Juvenile Breast Hypertrophy: A Successful Breast Reduction of 14.9% Body Weight without Recurrence in a 5-Year Follow-Up - Akmal Hisham; Marzida Abd Latib; Normala Basiron (Case Reports in Surgery)
Juvenile hypertrophy of the breast (JHB) is a rare and relentless disease affecting women in the peripubertal period. We present a 13-year-old girl with massive bilateral JHB, successfully treated with a breast reduction and free nipple graft technique. A total of 7300 grams of breast tissue had been removed, accounting for 14.9% of the patient’s total body weight. Prophylactic hormonal therapy was not commenced. During the 5-year follow-up period, there was no recurrence and the patient remains satisfied with the aesthetic outcome. A recent meta-analysis study indicates that subcutaneous mastectomy is associated with reduced risk of recurrence, but it is more deforming and the aesthetic result is inferior to a reduction mammaplasty. In patients treated with the latter technique, some evidence exists suggesting that the use of a free nipple graft is associated with a less frequent risk of recurrence than a pedicle technique. This present case is unique as it demonstrates the clinical course of this patient at a considerably longer follow-up period than most reported studies. We adhered to the limited available evidence and highlight the long-term reliability of breast reduction with free nipple grafting as the first line surgical option in JHB, eliminating the need for repeated surgeries.